KESESUAIAN PENYIMPANAN GOLONGAN NARKOTIKA DAN PSIKOTROPIKA DI FARMASI RUMAH SAKIT X DAERAH KEBAYORAN BARU JAKARTA SELATAN - sayyidah sayyidah; Agung Dewantoro; Bheta Sari Dewi; Ahmad Sopian (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
The hospital is one of the facilities that provide health services in an effort to maintain, improve health, prevent disease, cure disease, and recovering. Pharmaceutical services in hospitals have standards that must be met, namely regarding clinical pharmacy services and drug management. The formulation of the problems in this research are: How is the level of suitability for storing narcotics and psychotropic drugs at the Pertamina Central Hospital (RSPP) based on the Regulation of the Minister of Health Number 3 of 2015. This research uses a descriptive type, which is the most basic form of research. Intended to describe existing phenomena. This research examines the forms, activities, characteristics, changes, relationships, similarities, and differences between them and other phenomena. The results of this study indicate that the suitability of narcotics and psychotropic drugs is said to be good, the death stock of narcotics and psychotropic drugs is said to be good. The percentage of narcotics and psychotropic drugs that are expired or damaged are said to be good. The suitability of the Narcotics and Psychotropic drug dispensing system is not 100% FIFO and FEFO. The psychotropic storage system at the Pertamina Central Hospital Pharmacy Installation has met the Storage Standards based on the guidelines for the management of Hospital Pharmaceutical Supplies and the Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2015.